Prognostic factors for frequent episodic asthma in children - Noormanto, Sulaiman Hamid, Amalia Setyati, (Universitas Gadjah Mada, 2014)
Asthma is a major health problem affecting millions of children worldwide. The prevalence of asthmain children tends to increase annually in the world. Therefore, identification of the prognostic factorsfor episodic asthma is important to perform early prevention of asthma attacks in children. Thestudy was performed to identify the prognostic factors for frequent episodic asthma in children. Thiswas a retrospective cohort study involving asthmatic children who attended the Emergency Unit orOutpatient Clinic of the Department of Pediatrics, Dr. Sardjito General Hospital, Yogyakarta. Theinclusion criteria were asthmatic children aged over 7 years, suffering from asthma over 2 years andgetting agreement from their parents as expressed by signed an informed consent. The exclusioncriteria were children with other chronic obtructive pulmonary diseases beside asthma and childrenwith cardiovascular diseases. Subjects were grouped into two groups i.e. Case Group and ControlGroup. The Case Group was children with frequent episodic asthma while the Control Group waschildren with infrequent episodic asthma. Prognostic factors for episodic asthma were then gatheredby giving a questionnaire to their parents. Regression analysis was used to evaluate the relationshipbetween prognostic factors and episodic asthma. A total of 94 subjects comprising 37 (36.4%)subjects with frequent episodic asthma and 57 (63.6%) subjects with infrequent episodic asthmawere involved in the study. Furthermore, response to initial theraphy was significantly associatedwith frequent episodic asthma (RR= 8.64; 95%CI= 0.47-2.50; p=0.001). Whereas, nutritionalstatus, patients age when asthma diagnosed, exclusive breastfeeding, maternal education, exposureof secondhand smoke and welfare were not (p>0.05). In conclusion, the initial therapy is prognosticfactors for frequent episodic asthma in children.